Ideal maksimal fuzzy near-ring dan ideal prima fuzzy near-ring - ABDURRAHMAN, Saman ([Yogyakarta] : Universitas Gadjah Mada, 2010)
We discuss the fuzzy ideal of near-ring which includes a fuzzy maximal of near-ring and fuzzy prime ideal of near-ring. Futhermore it was studied the relationship between fuzzy maximal ideal of near-rings and fuzzy prime ideals of near-ring.